Implementation of Dose Monitoring Software in the Clinical Routine: First Experiences - Heilmaier, C.; Zuber, N.; Bruijns, B.; Ceyrolle, C.; Weishaupt, D. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: Radiation exposure of the public as a result of medical imaging has significantly increased during the last decades. To have a tool to register and control patient dose exposure, we implemented dose monitoring software at our institution and first connected our computed tomography (CT) scanners.Materials and Methods: CT dose data from July 2014 to February 2015 was retrospectively analyzed using dose monitoring software. We evaluated a number of scans above predefined dose thresholds (“alerts”), assessed reasons for alerts and compared data of two CT scanners, one located close to the emergency room (“emergency CT scanner”) and one mainly used on an outpatient basis (“clinical routine CT scanner”). To check for statistically significant differences between scanners, chi-square-tests were performed.Results: A total of 8883 scans were acquired (clinical routine CT scanner, n = 3415; emergency CT scanner, n = 5468) during which 316 alerts were encountered (alert quota, 4 %). The overall alert quota ranged from 2 – 5 % with significantly higher values for the clinical routine CT scanner. Reasons for alerts were high BMI (51 %), patient off-centering (24 %), scan repetition (11 %), orthopedic hardware (9 %), or other (5 %). Scan repetition was necessary significantly more often with the emergency CT scanner (p = 0.019), while high BMI, off-centering and orthopedic hardware were more frequently seen with the clinical routine CT scanner (for all, p < 0.05). There was a good correlation between high body weight and dose above threshold (r = 0.585).Conclusion: Implementation of dose monitoring software in the clinical routine was successfully accomplished and provides important information regarding patient radiation protection.Key Points:Citation Format:• Heilmaier C, Zuber N, Bruijns B et al. Implementation of Dose Monitoring Software in the Clinical Routine: First Experiences. Fortschr Röntgenstr 2016; 188: 82 – 88
Keywords: CT; radiation safety; QA/QC